Creative Economy-Based MSME Development Model Through Knowledge Management, Character Education, and Innovation as Intervening Variables - Triono, Triono; Syam, Mahmud Iqbal (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
MSMEs based on the creative economy certainly cannot be separated from the cooperation of various parties, in this case every sub-sector of the creative economy, because we have entered a new era, namely the birth of an era of the creative economy since 2001. Musi Rawas Regency has the potential of Micro, Small and Medium Enterprises (MSMEs) products based on a creative economy that need to be developed, ranging from fishery products, agriculture, handicrafts, livestock, food, and others. The purpose of this research is to examine and analyze business development strategies. Micro, Small and Medium Enterprises (MSMEs) based on creative economy in Musi Rawas Regency through Knowledge Management, Character Education, and Innovation as Intervening variables. The form of research used is causality research with quantitative approach. Causality research design is research thatdesigned to examine the possibility of a cause-and- effect relationship between variables. In this design, generally a cause-and-effect relationship is established predicted by the researcher, so that the researcher can state clarification causal variables, intermediate variables and related variables. This study aims to see the extent of the influence provided by Knowledge Management and Character Education on Creative Economy-based MSME Development, also through innovation as an intervening variable. The novelty of this research is that the researcher uses the intervening variable, namely innovation as an intermediary to further strengthen the influence exerted by the independent variable on the dependent variable. The results showed that Knowledge Management and Character Education had a positive and significant influence on the development of creative economy-based SMEs in Musi Rawas Regency. A greater influence is obtained through the innovation intervening variable, which means that knowledge management and character education will be better if combined with innovation so that it has a positive impact on the development of creative economy-based SMEs in Musi Rawas Regency.